Achieving Profitability of a Bank though Determining the Stages of Development of Innovative Loan Products - Chmutova Iryna M.; Andriichenko Zhanna O.; Kolesnichenko Anna S.; Kamsarian Mariam K. (Problemi Ekonomiki, 2020)
The aim of the article is to substantiate the approach to ensuring profitability of a bank by elaborating a strategy for enhancing its lending activity based on determining the stages of development of innovative loan products. The article presents the calculation of the indicators characterizing the intensification of lending and the lending policy, namely: share of loans to individuals in the loan portfolio, coefficient of lending activity, loan-to-deposit ratio and interest coverage ratio, for 73 banks of Ukraine as of 01.01.2020. Moreover, the dependence of a bank’s profitability on indicators of lending intensification is empirically confirmed though constructing a model using the principles of correlation and regression analysis. Innovations in the field of lending are systematized. It is determined that Ukrainian banks mainly sell such of them as deposit secured loans, overdrafts, revolving loan facilities, commercial real estate loans, express loans. To select strategies for intensifying bank lendingwith consideration for the stage of development of innovative loan products, it is proposed to apply the matrix technique. In view of this, the authors use a modified “life cycle balance matrix”. The types ofa bank’s lending strategies depending on its positioning in the matrix are identified through the correlation of the stages of development of loan products (entering the market, market development, stabilization, market decline) and levels of efficiency of its lending activity (low, medium, high). This will allow determining the period of decline in innovation in a timely manner and reorient towards products that have greater customer demand, which will ultimately help increase the bank’s profitability.